Hybridization Trends for Main Group Elements and Expanding the Bent’s Rule Beyond Carbon: More than Electronegativity - Alabugin, Igor V.; Bresch, Stefan; Manoharan, Mariappan (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2014)
Trends in hybridization were systematically analyzed through the combination of DFT calculations with NBO analysis for the five elements X (X = B, C, N, O, and F) in 75 H n X–YH m compounds, where Y spans the groups 13–17 of the periods 2–4. This set of substrates probes the flexibility of the hybridization at five atoms X through variations in electronegativity, polarizability, and orbital size of Y. The results illustrate the scope and limitations of the Bent’s rule, the classic correlation between electronegativity and hybridization, commonly used in analyzing structural effects in carbon compounds. The rehybridization effects are larger for fluorine- and oxygen-bonds than they are in the similar bonds to carbon. For bonds with the larger elements Y of the lower periods, trends in orbital hybridization depend strongly on both electronegativity and orbital size. For charged species, the effects of substituent orbital size in the more polarizable bonds to heavier elements show a particularly strong response to the charge introduction at the central atom. In the final section, we provide an example of the interplay between hybridization effects with molecular structure and reactivity. In particular, the ability to change hybridization without changes in polarization provides an alternative way to control structure and reactivity, as illustrated by the strong correlation of strain in monosubstituted cyclopropanes with hybridization in the bond to the substituent.